Kalcium- och fosforsmältbarhet hos växande hästar - Löf, Frida (SLU/Dept. of Animal Nutrition and Management (until 231231), 2013)
In the latest edition of NRC (2007) the feeding recommendations for Ca and P to growing horses were increased with 35 and 25 %, respectively, based on results from a Canadian study showing that daily endogenous fecal losses of Ca and P were greater than previously suggested. A Ca absorption efficiency of 50 % is used for all horses. However, the true absorption efficiency might be as high as 70 % in young horses. P absorption efficiency is assumed to be higher for growing horses because their diets are often supplemented with inorganic P. Thus, an efficiency of 45 % is used for growing horses as compared to 35 % for mature horses. The aim of this study was to measure the digestibility of Ca and P in some Swedish feedstuff in growing horses. An additional aim was to analyze the proportion of soluble P in horse feces. Four yearling Standardbred horses from Västerbo Stuteri were used in a cross-over design with two different diets. One diet consisted of roughage alone and one of roughage and oats. The trial started with a ten day adaptation period. Thereafter a collection period of six days followed when feces were collected 10 hours per day and total feed intake was registered. Feed and feces samples were analyzed for Ca and P to calculate digestibility and soluble P. The average apparent Ca and P digestibility did not differ between diets and were 63 ± 4 % and 23 ± 7 %, respectively, on the roughage-only diet and 49 ± 4 % and 21 ± 7 %, respectively, on the roughage and oats diet. Using regression analyses, daily endogenous fecal Ca and P were predicted to be 23 and 9 mg/kg body weight, respectively. The results from this study cannot confirm that the increase in Ca- and P-recommendations to growing horses (NRC, 2007) is justified but agrees with the results on which the previous NRC recommendations were based. The study also indicates that most of the P (92-93 %) in horse feces is soluble which mean that it should be gently handled to avoid environmental damage. It also implies that horse feces are a good P fertilizer.